Nutritional, physical and sensory characteristics of bread with the inclusion of germinated basul (Erythrina edulis) flour - Vilcanqui-Pérez, Fulgencio (2021)
The authors are thankful to the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT-Peru) for the financing granted pursuant to Contract No. 121-2018-FONDECYT-BM-IADT-SE.